Heat exchanger design handbook - Kuppan, T., 1957- (CRC Press, 2013)
"This comprehensive reference covers all the important aspects of heat exchangers (HEs): design and modes of operation and practical, large-scale applications in process, power, petroleum, transport, air conditioning, refrigeration, cryogenics, heat recovery, energy, and other industries. It includes over 400 drawings, diagrams, tables, and equations, making it a great resource for mechanical, chemical, and petrochemical engineers; process equipment and pressure vessel designers; and upper-level undergraduate and graduate students. This second edition includes updated material throughout; coverage of the latest advances in HE design techniques; expanded and updated coverage of materials selection; and a look at the newest fabrication techniques"-- Provided by publisher.
Keywords: Heat exchangers -- Design and construction -- Handbooks, manuals, etc.; elektronické knihy; electronic books